2015
DOI: 10.2119/molmed.2014.00265
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of sIgM-Mediated Intracellular Signaling through the CD180 Toll-like Receptor

Abstract: Chronic lymphocytic leukemia (CLL) development and progression are thought to be driven by unknown antigens/autoantigens through the B cell receptor (BCR) and environmental signals for survival and expansion including toll-like receptor (TLR) ligands. CD180/RP105, a membrane-associated orphan receptor of the TLR family, induces normal B cell activation and proliferation and is expressed by approximately 60% of CLL samples. Half of these respond to ligation with anti-CD180 antibody by increased activation/phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…The levels of cell surface CD180 are higher in CLL cases with mutated IGHV , making CD180, like CD150, a potential surrogate prognostic marker of CLL outcome [ 21 ]. CD180 ligation can modulate BCR signaling in CLL B cells, preventing pro-survival signals and inducing apoptosis [ 37 ]. We found that CD150 cell surface expression positively correlated with CD180 expression on CLL B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of cell surface CD180 are higher in CLL cases with mutated IGHV , making CD180, like CD150, a potential surrogate prognostic marker of CLL outcome [ 21 ]. CD180 ligation can modulate BCR signaling in CLL B cells, preventing pro-survival signals and inducing apoptosis [ 37 ]. We found that CD150 cell surface expression positively correlated with CD180 expression on CLL B cells.…”
Section: Discussionmentioning
confidence: 99%
“…As coreceptor molecule CD150 in CLL B cells can function alone or in cooperation with others cell surface receptors. Among them is CD180 that also is associated with mutational IGHV status and is involved in Akt and MAPK kinases activation [104][105][106]. CD180 is coexpressed and colocalized with CD150 on the cell surface membrane in around 60% of CLL cases.…”
Section: Cd150 Is a Candidate For Therapeutic Intervention In Leukemimentioning
confidence: 99%
“…The radioprotective 105 kDa protein (RP105) is a TLR4 homologue which lacks the intracytoplasmic Toll-IL-1 receptor (TIR) domain of TLR4 (21,22). RP105 is widely involved in the pathophysiological process of various cardiovascular diseases through directly inhibiting TLR4-driven pathogenesis during myocardial infarction, atherosclerosis and post-interventional vascular remodeling (22)(23)(24).…”
Section: Radioprotective 105 Kda Protein Attenuates Ischemia/reperfusmentioning
confidence: 99%